Synthesis of fluorinated maltose derivatives for monitoring protein interaction by 19F NMR - Braitsch, Michaela; Kählig, Hanspeter; Kontaxis, Georg; Fischer, Michael; Kawada, Toshinari; Konrat, Robert; Schmid, Walther (Beilstein Journal of Organic Chemistry, 2012)
A novel reporter system, which is applicable to the 19F NMR investigation of protein interactions, is presented. This approach uses 2-F-labeled maltose as a spy ligand to indirectly probe protein–ligand or protein–protein interactions of proteins fused or tagged to the maltose-binding protein (MBP). The key feature is the simultaneous NMR observation of both 19F NMR signals of gluco/manno-type-2-F-maltose-isomers; one isomer (α-gluco-type) binds to MBP and senses the protein interaction, and the nonbinding isomers (β-gluco- and/or α/β-manno-type) are utilized as internal references. Moreover, this reporter system was used for relative affinity studies of fluorinated and nonfluorinated carbohydrates to the maltose-binding protein, which were found to be in perfect agreement with published X-ray data. The results of the NMR competition experiments together with the established correlation between 19F chemical shift data and molecular interaction patterns, suggest valuable applications for studies of protein–ligand interaction interfaces.
Keywords: fluorination; 19F NMR; maltose-binding protein (MBP); maltose derivatives; protein interaction